Gerontechnology - FONSECA, CÉSAR (2020)
This book constitutes the thoroughly refereed post-conference proceedings of the First International Workshop on Gerotechnology, IWoG 2018, held in Cáceres, Spain on December 14, 2018, and in Évora, Portugal, on December 17, 2018. The 24 revised full papers along with 8 short papers presented were carefully reviewed and selected from 71 submissions.The papers are organized in topical sections on knowledge management for health: context, cognition, behavior and user modeling; technologies to increase the quality of life of the elderly population; Internet of Things (IoT); smarts technologies and algorithms for health; monitoring and management of chronic and non-chronic diseases;solutions for active aging, social integration and self-care; health interventions to support caregivers of elderly people; public health initiatives.